Tingkat Partisipasi Masyarakat Dalam Pengelolaan Dana Desa - Harefa, Emon Wirawan (Poltekkes Kemenkes Malang, 2024)
Community participation is vital for village development, especially in managing village funds. However, in Klapanunggal Village, the implementation of fund management still struggles to meet community needs due to insufficient involvement. This study aims to explore community participation in fund management and identify factors affecting it. Qualitative research methods were used, highlighting the importance of community involvement in public policy decisions. Despite government efforts to enhance participation, it remains low. While the community acknowledges the importance of involvement, their participation in implementation, evaluation, and benefit-taking processes remains limited, with minimal impact on daily life